(untitled) (Bangladesh Journal of Medicine, 2024)
Background: Coronary artery disease (CAD) is the leading cause of mortality, morbidity in the developed and developing country. Ageing is important risk factor for coronary artery disease. The role of conventional cardiovascular risk factors in older persons is incompletely understood because only fragmentary and inadequate data are available in most instance and manifestations of acute myocardial infarction are generally believed to be atypical in the elderly. The aim of the study was to find out the clinical presentation, common risk factors and In-hospital Outcome of Acute Myocardial Infarction in Elderly Patients. Methods: An observational study in tertiary level hospital. Study protocol was approved by ethical review committee of Sir Salimullah Medical College & Mitford Hospital, Dhaka. Sample was selected from the population by purposive sampling technique. Detail demographic data were collected from the subject and recorded in structured case report form. Researcher makes contact with patient and patients caregiver, and describe them about study aim-objective, and then informed consent was taken. All collected questionnaire checked very carefully to identify the error in the data. Data processing work were consisting of registration of schedules, editing, coding and computerization, preparation of dummy tables, analysis and matching data. Result: In this series, the maximum number of patients (57.0%) was between 60-69 years age group, with mean value 67.21 ± 9.05 years. Out of 100 cases (62%) cases were male and (38%) were female (Figure 1). Male – female ratio was 1.63:1. Large numbers of respondents came from urban area (58%). Among the patients the poor class (44%) comprising the major percentage of the myocardial infarction patients. In this study majority (58%) of the patients had sedentary lifestyle before the onset of myocardial infarction. Among all the risk factors hypertension was the most common risk factor, present in 62% cases; next common risk factors were Diabetes mellitus 56%, dyslipidemia 32%, obesity 22%, smoking 40%. In this study majority of patients (56%) presented with shortness of breath as predominant symptoms. Besides typical chest pain others important atypical symptoms were atypical chest pain (31%), upper abdominal pain (18%), giddiness (4%) and confusional state (3%). In this study many of the patients had developed acute LVF (34%), arrhythmia (17%), cardiogenic shock (8%). Conclusion: We concluded that the manifestations of AMI are more subtle in the elderly, with different risk factors. The elderly subjects are under thrombolysed and have higher complication rate. Bangladesh J Medicine 2024; 35(1): 9-14